Monopoly Practices Reviewed from the Perspective of Islamic Economics: a Systematic Review - Khairi, Fauzan Romadhian (RAFAHIYA Jurnal Ekonomi dan Syariah, 2025)
Background: This research aims to examine the Islamic economic perspective regarding monopoly practices. Monopoly practices amidst the free market trend have caused two impacts, namely benefits and losses. These two things are challenges for the government in maintaining market stability and balance.Method: This research uses the Systematic Literature Review (SLR) method guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). The time range of scientific publications used in this search is within the last ten years from 2014-2024. The author analyzes articles related to the topic of this paper and then extracts the main themes that appear in previous literature. This is useful for developing the next research agenda on the same topic by synthesizing one another so that lacuna or empty spaces are found that can be studied for subsequent research as an academic contribution to the topic of monopoly studies from an Islamic economics perspective.Results: The author identified 15 journal articles that met the predetermined inclusion criteria. Six articles are in English and nine articles are in Indonesian. The main themes identified are market balance, detrimental monopolies, state intervention, consumer protection, and business ethics. From existing and relevant research, after being analyzed using the SLR method and synthesizing one another, an academic gap or research gap (lacuna) was found in aspects of monopoly that are not detrimental from an Islamic economic perspective. For future research, it would be better to focus on monopolies permitted in Islamic Sharia so that a new perspective can be provided that accommodates the complex and dynamic dynamics of the modern economy.